Designing a toolkit for the assessment of Health in All Policies at a national scale in Iran - Damari, Behzad (Health Promot Perspect, 2020)
Background: Equitable promotion of health indicators requires cooperation among different sectors more than ever. The "Health in All Policies" (HiAP) approach contributes to this process through strengthening intersectoral collaboration. To implement this approach at a national scale, indicators of health-oriented performance from various organizations, and their measurement methods, need to be precisely defined. The aim of present study was to design a toolkit for implementing HiAP in Iran. Methods: A review of literature and documents, as well as conducting semi-structured interviews and focus group discussions were undertaken to collect data for this qualitative study. Content analysis was applied to the collected data and the results were placed in three categories: criteria, sub-criteria and indicators; implementation processes; and implementation requirements. Results: The toolkit aims to achieve various objectives, including intersectoral excellence and the systematic development of intersectoral collaboration. In the process section, reports on measures taken by organizations are assessed by a three-member audit committee. The top three organizations, in terms of intersectoral cooperation in achieving public health goals, are introduced in a Health Week. Requirements for success in achieving the HiAP approach include financial resources to implement the HiAP, a database, an electronic method for submitting reports, training courses, monitoring and annual reporting of relevant indicators, and formulating regulations in order to assess organizations. Conclusion: Justification and training in various organizations to support the implementation of health-oriented measures, providing an annual ranking of organizations, and encouraging the organizations can contribute to the institutionalization of the toolkit through the SupremeCouncil for Health and Food Security. It is recommended that a Secretariat of sustainable development to be established under the Plan and Budget Organization (PBO) of the Islamic republic of Iran to monitor portfolio indicators.